(untitled) (Global Journal of Management and Business Research, 2020)
The publication intents to examine the impact of entrepreneurial activities on natural capital. The main objective of entrepreneurs is to grow their wealth. Such wealth is Increased through exploitation and depletion of natural capital on one end and pollution of natural capital stocks like air and water on the other. The publication gives a detailed analysis of the composition of natural capital and how these are depleted and polluted as humanity goes about his economic activities. The qualitative research methodology was found most suitable for the study. Various source provided the necessary data. Where appropriate, interviews and observation methods were Used to gain further insights on the subjects. Authenticity, creditability, representativeness and meaning underpinned the selection of the sources of data. The author posits that entrepreneurs should innovate on business models that endure and get rid of those models that burn out in order to achieve sustainable development.